The digital revolution amidst the crowing of roosters: The determining factor for the technological transformation of the kendal "master pitung" chicken farmer - Utami Puji Lestari; Marsiska Ariesta Putri; Regita Sekar Nawang Fresia; Fidriani Fidriani (International Journal of Applied Finance and Business Studies, 2025)
The background of the digital revolution in the chicken farming industry is driven by the urgent need to improve efficiency, overcome operational challenges, and meet increasing market demand. This study has three main objectives, namely, analyzing the influence of financial literacy, digital access, and the characteristics of micro, small, and medium enterprises (MSMEs) on the adoption of peer-to-peer (P2P) lending platforms and access to MSME financing; evaluating the direct influence of the adoption of P2P lending platforms on access to MSME financing; and evaluating whether financial technology (fintech) regulations moderate the relationship between the adoption of P2P lending platforms and access to MSME financing. Quantitative research methods were used, with a causality and correlation survey design. The results of the study indicate that financial literacy, digital access, and MSME characteristics have a positive effect on the adoption of P2P lending platforms. In addition, the adoption of P2P lending platforms has a positive effect on access to MSME financing. However, fintech regulations do not moderate the relationship between the adoption of P2P lending platforms and access to MSME financing. Financial literacy, digital access, and MSME characteristics also have a positive effect on access to MSME financing.